2012
DOI: 10.1371/journal.pone.0030259
|View full text |Cite
|
Sign up to set email alerts
|

Anti- Japanese-Encephalitis-Viral Effects of Kaempferol and Daidzin and Their RNA-Binding Characteristics

Abstract: BackgroundNew therapeutic tools and molecular targets are needed for treatment of Japanese encephalitis virus (JEV) infections. JEV requires an α-1 translational frameshift to synthesize the NS1' protein required for viral neuroinvasiveness. Several flavonoids have been shown to possess antiviral activity in vitro against a wide spectrum of viruses. To date, the antiviral activities of flavonol kaempferol (Kae) and isoflavonoid daidzin (Dai) against JEV have not been described.Methodology/Principal FindingsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 45 publications
4
58
2
3
Order By: Relevance
“…Indeed, it was demonstrated that baicalein increased the in vitro and in vivo antiviral activity of ribavirin against influenza virus significantly [24]. Recently, through theantiviral activity of kaempferol and daidzin, two types of flavonoids against Japanese encephalitis virus were reported [11]. In the present study we also have demonstrated that baicalein exhibited potent in vitro anti-JEV effects at all different stages of JEV infection compared to the quercetin.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Indeed, it was demonstrated that baicalein increased the in vitro and in vivo antiviral activity of ribavirin against influenza virus significantly [24]. Recently, through theantiviral activity of kaempferol and daidzin, two types of flavonoids against Japanese encephalitis virus were reported [11]. In the present study we also have demonstrated that baicalein exhibited potent in vitro anti-JEV effects at all different stages of JEV infection compared to the quercetin.…”
Section: Discussionsupporting
confidence: 75%
“…There have been efforts to find effective antiviral substance among the natural compounds such as plant or algal derived compounds [9,10]. Recently, in vitro anti-JEV activities of two different types of bioflavonoids namely kaempferol and daidzin were evaluated and it was shown that kaempferol is more effective against JEV replication compared to daidzin [11]. Compounds from natural resources are regarded as possible alternatives as they may show low side effects and easily accessible from nature.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin, a member of the flavonol subgroup of flavonoids, is capable of inhibiting influenza virus, dengue virus, and JEV [36], [37], [38]. The antiviral activities of kaempferol and daidzin against JEV were also reported by our lab [39]. But to the best of our knowledge, no study has investigated the antiviral properties of HF and FIP from the flavone subgroup in vivo or in vitro.…”
Section: Discussionmentioning
confidence: 85%
“…[94,95] Minocycline Antioxidant [99,100] Arctigenin Antioxidant [101] Fenofibrate Antioxidant [102] Curcumin Antioxidant [103] Pentoxifylline Assembly or Release [105] Nitazoxanide Early/mid-replication cycle [107] Nucleic acid-based siRNA C, M, E, NS1, NS3, NS4B, NS5 [109][110][111][112][113][114][115] PNA UTR [119] Morpholino oligomer UTR [121,122] Virus replication cycle-based Heparan sulfate Receptor binding [123][124][125] E-binding peptide Receptor binding [126] NSQ Attachment [127] Indirubin Attachment [128] Bovine lactoferrin Receptor binding [129] Griffithsin Receptor binding [130] Recombinant E Receptor binding [131,132] MCPIP1 RNA replication [133] Kaempferol RNA replication [134] SCH16 Translation [138,139] In silico modeling-based Ivermectin NS3 [146] 4-hydroxypanduratin NS2B/NS3 [147] C randomized, double-blind, human clinical trial conducted in India [95]. A variety of virus-infected cells have been shown to produce reactive oxygen species (ROS), which are associated with viral pathogenicity, for example, by inducing cellular apoptosis [96].…”
Section: Categorymentioning
confidence: 99%
“…Monocyte chemoattractant protein 1-induced protein 1 (MCPIP1), which contains a nuclease domain, displays anti-JE activity in vitro, and the RNase, RNA-binding and oligomerization properties of MCPIP1 are required for its anti-JE activity [133]. Kaempferol, a polyhydric flavonol derived from various plants, inhibits JEV replication by binding to the viral genome in vitro [134]. FGIN-1-27, cilnidipine, niclosamide and bispidine--amino acid conjugates displayed anti-JE activities in vitro, probably by inhibiting RNA replication [135,136].…”
Section: Viral Replication Cycle-based Antiviral Drugsmentioning
confidence: 99%